Considering the marketing of higher education: the role of student learning gain as a potential indicator of teaching quality. Issue 2 (3rd July 2017) - Polkinghorne, Martyn; Roushan, Gelareh; Taylor, Julia
ABSTRACT: The marketization of higher education has ensured that students have become consumers. As a result, students are demanding increased levels of information regarding potential university courses so that they can make informed decisions regarding how best to invest their money, time and opportunity. A comparison of the teaching quality delivered on different programs of study will be an important element of this decision-making process. The Teaching Excellence Framework proposes that teaching quality will be assessed by measures including the evaluation of student learning gain. This paper reflects on an analysis of consultation responses from key stakeholders across the UK higher education sector to determine how evaluating learning gain could be effectively achieved. Synthesizing these responses, ten key considerations regarding evaluating learning gain have been identified that together provide a unique perspective to ensure that any evaluation of student learning gain subsequently undertaken is relevant to the marketing of higher education.